2023
DOI: 10.1021/acsnano.3c05298
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Nanoparticles for Modulating Arthritis Flares

Wade T. Johnson,
David McBride,
Matthew Kerr
et al.

Abstract: Disease-modifying drugs have improved the treatment for autoimmune joint disorders, such as rheumatoid arthritis, but inflammatory flares are a common experience. This work reports the development and application of flare-modulating poly(lactic-co-glycolic acid)-poly(ethylene glycol)-maleimide (PLGA-PEG-MAL)-based nanoparticles conjugated with joint-relevant peptide antigens, aggrecan 70−84 and type 2 bovine collagen 256−270 . Peptide-conjugated PLGA-PEG-MAL nanoparticles encapsulated calcitriol, which acted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…We compared model predictions to lymph node and ankle T cell counts in the T cell-driven SKG model of autoimmune arthritis from datasets previously generated and published by our group. 44,45 Comparison of model results to in vivo data showed that T cell proliferation in the lymph node follows a similar trend to model predictions in the range of m = 800–1000 TCR-ad values (Fig. 2g).…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…We compared model predictions to lymph node and ankle T cell counts in the T cell-driven SKG model of autoimmune arthritis from datasets previously generated and published by our group. 44,45 Comparison of model results to in vivo data showed that T cell proliferation in the lymph node follows a similar trend to model predictions in the range of m = 800–1000 TCR-ad values (Fig. 2g).…”
Section: Resultssupporting
confidence: 59%
“…The dynamics of T cell activation modeled by ABCD of IA are well supported by prior in vivo results from arthritic SKG mice. 44,45 Prior work from animal models has established that activated DCs contribute to the development of IA pathology. 55 Adoptive transfer of autoantigen-primed DCs have been shown to expand disease-specific T cells in the joint-draining lymph node in mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations